Thyroid Autoimmunity: Role of Anti-thyroid Antibodies in Thyroid and Extra-Thyroidal Diseases - Fröhlich, Eleonore; Wahl, Richard (Frontiers in Immunology, 2017)
Autoimmune diseases have a high prevalence in the population and autoimmune thyroid disease (AITD) is one of the most common representatives. Thyroid autoantibodies are frequently detected in patients with AITD but also in subjects without manifest thyroid dysfunction. The high prevalence raises questions regarding a potential role in extra-thyroidal diseases. This review summarizes the etiology and mechanism of AITD and addresses prevalence of antibodies against thyroperoxidase, thyroid stimulating hormone receptor and anti-thyroglobulin and their action outside the thyroid. The main issues limiting the reliability of the conclusions drawn here include problems with different specificities and sensitivities of the antibody detection assays employed, as well as potential confounding effects of altered thyroid hormone levels, and lack of prospective studies. In addition to the well-known effects of thyroid stimulating hormone receptor antibodies on fibroblasts in Graves’ disease, studies speculate on a role of anti-thyroid antibodies in cancer. All antibodies may have a tumor-promoting role in breast cancer carcinogenesis despite anti-thyroperoxidase antibodies having a positive prognostic effect in patients with overt disease. Cross-reactivity with lactoperoxidase leading to induction of chronic inflammation might promote breast cancer, while anti-thyroid antibodies in manifest breast cancer might be an indication for a more active immune system. A better general health condition in older women with anti-thyroperoxidase antibodies might support this hypothesis. The different actions of the anti-thyroid antibodies correspond to differences in cellular location of the antigens, titers of the circulating antibodies, duration of antibody exposure, and immunological mechanisms in Graves’ disease and Hashimoto’s thyroiditis.